LEGALITAS KAYU DARI HUTAN ADAT: STUDI KASUS DI NEGERI HONITETU, SERAM BAGIAN BARAT, MALUKU - Fentie Jullianti Salaka; Didik Suharjito; Satria Astana; Martina Tjoa (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2018)
Timber Legality Verification System (TLVS) policy requires all forest management business units in either state forests or private forests, including customary forests to obtain timber legality certificate. The purpose of this study to determine the fulfillment of timber legality according to customary rules and TLVS. The method used was a case study conducted in Negeri Honitetu, West Seram, Maluku. The results showed that TLVS policy is not implementable if it is applied to the utilization  of timber from customary forests in Negeri Honitetu, since local customary people do not have the documents as required in the TLVS. Timber utilization from customary forests in Negeri Honitetu has been carried out by referring  to the prevailing customary rules, namely (1)  felled trees are in the cultivation area and obtain permission from the Head of Dati, (2) outside of the sacred area, (3) profit sharing for  all members of  dati, and (4) free of charge if it is used to meet the needs of the community itself and the public interest. The study recommend to facilitate local customary people into social forestry schemes by providing protection for the preservation of natural resources as well as protection of the rights of local customary people.